The Improvement of The Self-Care Agency for Patients with Ischemic Stroke After Applying Self–Care Regulation Model in Nursing Care - AV. Sri Suhardingsih; Moh. Hasan Mahfoed; Rahmat Hargono; Nursalam Nursalam (Universitas Airlangga, 2012)
Introduction: The patiens with ischemic stroke caused a dependence in a need of self-care for the aspect of physically, psychologically, socially and spiritually. Nursing care approach will encourage patiens to became independence in self-care. The purpose of this research was to examine the improvement of the self care agency of the patients with ischemic stroke after aplying a nursing care of self care regulation model.Method: An experimental research with quasy experimental design was applied in the study. The study was conducted in the area of Surabaya by selecting 40 patients of ischemic stroke being hospitalized in stroke Unit IRNA MEDIK RSUD Dr. Soetomo Surabaya and selected by consecutive sampling. Sample of 40 patients were divided equally into two groups, namely treatment and control groups. The selection of sample was matching based on age and sex. Independent variable in the study were self-care regulation: interpretation coping and appraisal. While dependent variable was self-care agency of the patients with ishemic stroke. Data was analysed by wilcoxon signed rank, Mann-Whitey test and modeling by SEM - PLS.Result: The result showed that there were significant differences on the increase of self care agency between the groups. The group model that aplying a nursing care of self-care regulation gained the value of R2 = 0.857 and the standart nursing care gained the value of R2 = 0.614, so it could be inferred that the best model was self care regulation model, with the differentiation R2 = 0.243.Discussion: It was concluded that the nursing care of self care regulation model could self-care agency up to 24.3% than the standard of nursing care. It is recomended that Self-care regulation model can be used as a standard of nursing care in health care institutions both in hospitals and in clinics.